2021
DOI: 10.1111/jcpe.13486
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted and targeted gingival metabolome in rodents reveal metabolic links between high‐fat diet‐induced obesity and periodontitis

Abstract: Aim: To characterize gingival metabolome in high-fat diet (HFD)-induced obesity in mice with/without periodontitis.Methods: HFD-induced obesity mouse model was established by 16-week feeding, and a lean control group was fed with low-fat diet (n = 21/group). Both models were induced for periodontitis on the left sides by molar ligation for 10 days, whereas the right sides were used as controls. Gingival metabolome and arginine metabolism were analysed by non-targeted/targeted liquid chromatography-mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Compared with healthy counterparts, periodontitis and a high-fat diet had distinct effects on the gingival metabolome. The metabolomic impact of periodontitis was generally greater in high-fat diet mice than in lean controls [92]. Another study performed fecal microbiota transplantation and ligature-induced periodontitis in mice with high-fat diet-induced obesity and demonstrated that gut dysbiosis-associated metabolites from high-fat diet-fed mice worsen alveolar bone destruction.…”
Section: Diabetes and Obesity Model Mice With Ligature-induced Periodontitismentioning
confidence: 99%
“…Compared with healthy counterparts, periodontitis and a high-fat diet had distinct effects on the gingival metabolome. The metabolomic impact of periodontitis was generally greater in high-fat diet mice than in lean controls [92]. Another study performed fecal microbiota transplantation and ligature-induced periodontitis in mice with high-fat diet-induced obesity and demonstrated that gut dysbiosis-associated metabolites from high-fat diet-fed mice worsen alveolar bone destruction.…”
Section: Diabetes and Obesity Model Mice With Ligature-induced Periodontitismentioning
confidence: 99%
“…More and more research evidence shows that the changes of gut microbiota affect the levels of metabolites, leading to the development of insulin resistance, atherosclerosis, and other diseases ( Lin and Zhang, 2017 ; Canfora et al, 2019 ; Verhaar et al, 2020 ). Chen et al (2021) showed that compared with healthy controls, periodontitis and high-fat diet had a significant impact on gingival metabolome, and experiments verified that high-fat diet had a superimposed effect on metabolome such as arginine metabolism in the presence of periodontitis. A recent animal study suggested that the periodontal pathogen P. gingivalis may increase insulin resistance and circulating branched-chain amino acids elevation through its metabolic activity ( Tian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“… Sakanaka et al (2021) explored the potential link between periodontitis and cardiometabolic diseases by studying metabolites. Previous studies have pointed out that the use of metabolomics to study the relationship between periodontitis and obesity gets significantly more outputs than the pure oral microbiome ( Chen et al, 2021 ). At present, 16S rDNA sequencing technology is mostly used in the analysis of the gut microbiome, but this technology has the limitation of lacking quantitative functional annotation.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have indicated that an increased alveolar bone loss in obese animals with PD and significantly greater alveolar bone loss in obese rats than in lean controls ( 12 , 13 ). In addition, obese individuals who consume an excessively high-fat diet have an enhanced metabolic response to PD and show a metabolic susceptibility to increased periodontal destruction ( 14 ). These findings highlighted the existence of an association between OB and PD.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of clinical and experimental evidence suggests that immune cell infiltration and inflammatory factors play a critical role in the development of OB or PD ( 2 , 14 ). On the one hand, mouse models of OB and diabetes were found to be characterized by impaired T and B lymphocyte-mediated immune responses ( 2 ).…”
Section: Introductionmentioning
confidence: 99%